Analisis Pengaruh CAR, NPL dan NIM terhadap Profitabilitas Perbankan yang Terdaftar di Bursa Efek Indonesia - Luh Nadi (Jurnal Ilmiah Akuntansi Universitas Pamulang, 2016)
This study aims to determine the effect of CAR, NPL, and NIM to profitability using a measuring instrument ROA in banks which had assets above Rp 100 trillion and is listed on the Indonesia Stock Exchange (BEI) in the period 2010 - 2014. This study uses regression analysis Data panel, where the panel data obtained from the combined data of cross section data (N), there are ten (10) companies and time series (t), there are 5 years. Thus, in this study there were 50 observational data. The result of the calculation of the effect of CAR on ROA, obtained by value t count <t-table (0,348 <2.0129) with significant value 0.7297> 0.05, CAR does not mean positive effect on ROA. NPL influence on ROA calculation, obtained by value t count <t-table (-3.055 <-2.0129) with significant value 0.0037 <0.05, which means NPL has negative effect on ROA. While calculating the effect NIM on ROA, obtained by value t count> t-table (2.939> 2.0129) with significant value 0.0051 <0.05, which means NIM. Ha the positive effect on ROA